2010
DOI: 10.1128/jvi.00572-10
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Mapping of UL130 of Human Cytomegalovirus Defines Peptide Motifs within the C-Terminal Third as Essential for Endothelial Cell Infection

Abstract: The UL130 gene is one of the major determinants of endothelial cell (EC) tropism of human cytomegalovirus (HCMV). In order to define functionally important peptides within this protein, we have performed a chargecluster-to-alanine (CCTA) mutational scanning of UL130 in the genetic background of a bacterial artificial chromosome-cloned endotheliotropic HCMV strain. A total of 10 charge clusters were defined, and in each of them two or three charged amino acids were replaced with alanines. While the six N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…This was a surprising result and stands in stark contrast to the reports that similar CCTA mutagenesis of the UL128-131 proteins greatly disrupted gH/gL/UL128-131 (54)(55)(56). Given that gH/gL/UL128-131 likely binds cell type-specific receptors to facilitate infection (21,22), these observations suggest that the receptor-binding surfaces lie on UL128-131 themselves and gH/gL may serve as a scaffold or platform for presentation of the UL128-131 proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…This was a surprising result and stands in stark contrast to the reports that similar CCTA mutagenesis of the UL128-131 proteins greatly disrupted gH/gL/UL128-131 (54)(55)(56). Given that gH/gL/UL128-131 likely binds cell type-specific receptors to facilitate infection (21,22), these observations suggest that the receptor-binding surfaces lie on UL128-131 themselves and gH/gL may serve as a scaffold or platform for presentation of the UL128-131 proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…The finding that virtually all parts of the UL131A protein are relevant for endothelial cell infection is supported by comparison of the amino acid sequence of pUL131A in clinical isolates of HCMV from different geographical regions that showed that the pUL131A sequence of 11 of 12 clinical isolates is absolutely identical (data not shown). In contrast, comparison of the amino acid sequence of pUL130 in the same clinical isolates showed variation in 12 amino acid positions, mainly in the N-terminal and central part of pUL130, and the function for EC tropism was mapped to the C-terminal third of pUL130, which was again highly conserved (22).…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, a peptide containing charge cluster pUL131A [91][92][93][94][95][96][97][98] has recently been successfully used to induce neutralizing antibodies in rabbits (20), hence arguing against extended mutation of this epitope for vaccine development. However, as we have previously defined similar mutations with partial effects on the EC tropism in UL128 and UL130 (22,23), combinations of mutations in different genes are also feasible and may result in an immunogenic mutant that is robust against spontaneous genetic reversion and displays strongly reduced but not completely abrogated replication potential in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations